(untitled) - Fusfeld, Herbert I. (Cambrigde, 1986)
By this book, Fusfeld provides an understanding of the forces for change within the technological system and the changes that are occurring today due to these forces
Keywords: Technological innovations,Đổi mới công nghệ,High technology industries,Công nghiệp kỹ thuật cao; Economic aspect,Khía cạnh kinh tế